Pendampingan Pembuatan Brand dan Konten Marketing untuk Ibu – Ibu PKK Desa Imogiri - Nadalia Silmi Fathinah; Kiki Sipa’ul Hafid; Permata Dian Pratiwi; Addien Ismi Fadhilah; Melani Nur Anggraini; Cahyo Dwi Prastowo; Voettie Wisataone; Ulfah Hidayati; Suranto AW (Universitas Pendidikan Indonesia Kampus Purwakarta, 2023)
In new normal era, PKK Imogiri Bantul were feeling the impact caused by Covid-19. PKK women used WhatsApp stories to sell and promote their wares. However, digital marketing skills and abilities are needed to survive in this new normal era. Content marketing in digital marketing through social media has an important role in increasing attractiveness to consumers. The purpose of assisting in brand creation and marketing content is expected to increase product sales and expand the market segment of PKK women. The method of implementing this service activity is offline mentoring by complying with Health protocols and online mentoring through the whatsapp group. The evaluation showed 80% participants understood about well brand.